‘They were extraordinary circumstances’: Biopolitics, medicine and the state of exception in NBC’s The West Wing - Kasper, Daniel (Journal of Popular Television, The, 2019)
In the final moments of NBC’s series The West Wing (1999–2006), the camera briefly shows a copy of Michel Foucault’s Society Must Be Defended ([1992] 2003) sitting on a bookshelf in the fictionalized Oval Office. Coming as it does at the end of the series, Foucault’s work becomes an interlocutor of the issues, political and personal, that the show explores. Given that Foucault’s work is his first to take up biopolitics in his lectures at the College de France, its inclusion gives viewers an opportunity to explore how The West Wing grapples with the open questions of sovereignty and biopolitics in the neo-liberal, post-9/11 present of the series and of the historical moment. This article addresses these questions with a combination of Foucault’s work and Giorgio Agamben’s concept of the ‘state of exception’. By focusing mainly on two episodes – ‘17 People’ and ‘Dead Irish Writers’ – as well as the antecedent and subsequent narrative threads, the conflicts between the ancient regime of the king’s two bodies and the modern technology of biopower become clear. The biopolitical healthcare of the president’s body, I argue, complicates the clarity of the sovereign power of the president, allowing other political actors – the first lady especially – access to the state of exception. Ultimately, though the show does not offer us a pathway to liberation, it begins the arduous process of escaping from the king’s two bodies.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qcHR2LjcuMS4yNV8x